EUROPEAN MISSILE DEFENSE AS A NEW FORM OF INTERNATIONAL COOPERATION OF USA ON MISSILE DEFENSE - E. A. Degtereva (Vestnik MGIMO-Universiteta)
This article examines U.S. efforts to build a broad international coalition in the area of missile defense. The basic formats of military cooperation with foreign countries in the deployment of the U.S. global missile defense system are described, as well as the principles of cooperation on the part of the United States. A review of the regional missile defense systems created by the United States as an intermediate step on the way to a global missile defense system is provided. Particular emphasis is placed on the implementation of The Phased Adaptive Approach for Missile Defense in Europe (European Phased Adaptive Approach, EPAA) and the creation of Active Layered Theater Ballistic Missile Defense (ALTBMD). Specified milestones and activities under the program, as well as the practical difficulties faced by the U.S. and European countries to deploy missile defense in the context of the global economic crisis are analyzed.